2009
DOI: 10.1038/clpt.2009.61
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant Pharmacodynamic Analysis of Immunosuppressive Agents Using CFSE-Based T-Cell Proliferation Assay

Abstract: The impact of pretransplant T-cell sensitivity testing using carboxylfluorescein diacetate succinimidyl ester (CFSE)-based flow cytometry was studied in 32 patients with chronic renal failure. There was considerable interindividual variation in the inhibitory effects of cyclosporine (CSA), tacrolimus (TAC), and prednisolone (PRD) but only a small amount of interindividual variation for mycophenolic acid (MPA). Patients with high sensitivity to CSA tended to experience viral reactivation. In addition to post-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Tirona and colleagues have identified OATP1B1 (SLCO1B1) as a liver-specific uptake transporter for statins, carrying frequent singlenucleotide polymorphisms with impaired function. 3 These findings translate into changes of pharmacokinetics in vivo (i.e., increased systemic concentrations as a consequence of reduced liver uptake), especially in individuals harboring the frequent c.SLCO1B1 521C→T polymorphism, which is associated with reduced function. Pharmacokinetic consequences of this polymorphism are important but rather modest, and they translate into only minor effects involving LDL reduction.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Tirona and colleagues have identified OATP1B1 (SLCO1B1) as a liver-specific uptake transporter for statins, carrying frequent singlenucleotide polymorphisms with impaired function. 3 These findings translate into changes of pharmacokinetics in vivo (i.e., increased systemic concentrations as a consequence of reduced liver uptake), especially in individuals harboring the frequent c.SLCO1B1 521C→T polymorphism, which is associated with reduced function. Pharmacokinetic consequences of this polymorphism are important but rather modest, and they translate into only minor effects involving LDL reduction.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…2 These new entrants include the incretin-based therapies (e.g., GLP-1 analogs such as exenatide and liraglutide); DPP4 inhibitors such as sitagliptin, vildagliptin, and saxagliptin; glucokinase activators such as piragliatin, LY2121260, and GKA-50; and FGF21 mimetics. 3 Given the diversity of mechanisms of action and the range of target perspec tives possible relationships between the various outcome measures (e.g., adiponectin and HbA1c). This approach is superior to the common practice of examining only study-level data by meta-regression.…”
Section: Biomarkers Linked To Patient Outcomes (Safety and Efficacy) mentioning
confidence: 99%
“…Several approaches have been evaluated to measure the biological effect of Tac and CsA: drug‐specific pharmacodynamic biomarkers, such as measurement of calcineurin phosphatase activity, nuclear translocation of nuclear factor of activated T cells (NFAT), amplification of NFATc1 and NFAT‐regulated gene expression (NFAT‐RGE), and other non‐specific biomarkers, such as intracellular cytokines . T cell proliferation and surface activation markers …”
Section: Introductionmentioning
confidence: 99%
“…11,12 T cell proliferation and surface activation markers. 13,14 It is well known that CNi inhibits NFAT translocation to the nucleus in CD4 + and CD8 + T cells, reducing the transcription of the genes it regulates, including interleukin-2 (IL-2), interferon-gamma (IFN-γ) and granulocyte macrophage colony-stimulating factor (GM-CSF); these changes in transcription modulate the alloimmune response against the implanted graft. 15,16 Focusing on the analysis of residual NFAT-RGE, several studies carried out in stable kidney transplant recipients have shown an inverse correlation between Tac or CsA blood concentrations and NFAT-RGE of IL-2, IFN-γ and GM-CSF 10,17,18 Results from a single randomized prospective interventional study (EudraCT 2011-003547-21) conducted in stable kidney transplant recipients 19 showed that reducing the CsA doses, and therefore the drug exposure, according to the NFAT-RGE results could be a useful tool to reduce cardiovascular risk compared with standard dose adjustment based on CsA trough levels.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study indicated that CSA and prednisolone had considerable inter-individual variation in their inhibitory effects on T-cell proliferation. 25) A more recent study demonstrated that CMV reactivation and acute T-cell mediated rejection were significantly associated with the CSA sensitivity of lymphocytes. 26) These studies suggested that not only the drug concentration in lymphocytes, but also the drug sensitivity affecting lymphocyte proliferation could influence the clinical outcome.…”
Section: )mentioning
confidence: 99%